Smoking prevalence and economic crisis in Brazil - Souza, Luis Eugenio de; Rasella, Davide; Barros, Rafael; Lisboa, Erick; Malta, Déborah; Mckee, Martin (Revista de Saúde Pública, 2021)
OBJECTIVE: To estimate the impact of the 2015–2018 economic crisis on tobacco consumption in Brazil. METHODS: This is an interrupted time series analysis conducted with data from 27 cities collected by VIGITEL, using linear regression models to account for first-order autocorrelation. Analyses were conducted based on gender, age group, and education level. RESULTS: Smoking rates decreased between 2006 and 2018, decelerating after the crisis onset. Differently than women, men showed an immediate but transient increase in smoking, followed by a decelerated decrease. Those over 65 also showed increased smoking rates immediately after the economic crisis onset, but decline accelerated later on. In turn, we found a trend reversal among those aged 31–44. Rates also decreased among those with lower education levels, but decelerated among those with more years of schooling. CONCLUSION: An economic crisis have varied impacts on the smoking habits of different population groups. Tobacco control policies should entail a detailed understanding of smoking epidemiology, especially during an economic crisis. DESCRIPTORS: Tobacco Use Disorder, epidemiology. Poverty. Health Impact Assessment. Financial Management